2011
DOI: 10.1186/1471-2180-11-237
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis infection induces non-apoptotic cell death of human dendritic cells

Abstract: BackgroundDendritic cells (DCs) connect innate and adaptive immunity, and are necessary for an efficient CD4+ and CD8+ T cell response after infection with Mycobacterium tuberculosis (Mtb). We previously described the macrophage cell death response to Mtb infection. To investigate the effect of Mtb infection on human DC viability, we infected these phagocytes with different strains of Mtb and assessed viability, as well as DNA fragmentation and caspase activity. In parallel studies, we assessed the impact of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Cell viability was assessed using the propidium iodide (PI) exclusion method for plasma membrane integrity of cells, and the nuclei were counterstained with Hoechst as previously described by us (24,26). The number of PI-positive cells relative to the total number of nuclei per field was counted by automated fluorescence microscopy using the IN Cell Analyzer 1000 and IN Cell Investigator software (GE Healthcare, Pittsburgh, PA).…”
Section: Propidium Iodide and Hoechst Assaymentioning
confidence: 99%
“…Cell viability was assessed using the propidium iodide (PI) exclusion method for plasma membrane integrity of cells, and the nuclei were counterstained with Hoechst as previously described by us (24,26). The number of PI-positive cells relative to the total number of nuclei per field was counted by automated fluorescence microscopy using the IN Cell Analyzer 1000 and IN Cell Investigator software (GE Healthcare, Pittsburgh, PA).…”
Section: Propidium Iodide and Hoechst Assaymentioning
confidence: 99%
“…(4) PAMPs can induce the release of DAMPs: thus infection processes, such as infection of airway epithelial cells by respiratory syncytial virus, induce the release of hsp27, activating neutrophils via TLR4, 43 and DCs infected with M. tuberculosis undergo caspase‐independent cell death that allows the release of inflammatory DAMPs, not impeded by caspase neutralization 44 …”
Section: Defining the Inflammatory Response By The Interplay Between mentioning
confidence: 99%
“…(4) PAMPs can induce the release of DAMPs: thus infection processes, such as infection of airway epithelial cells by respiratory syncytial virus, induce the release of hsp27, activating neutrophils via TLR4, 43 and DCs infected with M. tuberculosis undergo caspaseindependent cell death that allows the release of inflammatory DAMPs, not impeded by caspase neutralization. 44 Owing to similarities to IL-1a and HMGB1 in regard to constitutive nuclear expression and passive release, it has been suggested that IL-33 is a member of the alarmin (or DAMPs) family, 45 and the active release of IL-33 by macrophages can be triggered by PAMPs, such as LPS. 46 Taking all this into account, we assemble a tentative PAMP-DAMPbased inflammatory code.…”
Section: Defining the Inflammatory Response By The Interplay Between mentioning
confidence: 99%
“…Following 24 h incubation, cells were stained simultaneously with 5 mg/ml Propidium Iodide (PI), 20 mg/ml Hoechst 33342 and 50 mg/ml Hoechst 33258, briefly resuspended by gentle pipetting, then plates were centrifuged at 4006g for 2 min to bring cells in suspension to the bottom surface of the well. Plates were then imaged using an INCell Analyzer 1000 cellular imaging system (GE Healthcare) and images were analyzed using GE INCell Analyzer 1000 Workstation software version 3.6 (GE Healthcare) as we have previously published [21]. Total cell numbers were detected via Hoechst staining of nuclei, and the dying/dead cells were identified via positivity for PI staining and/ or nuclear condensation, which was characterised by elevated intensity of Hoechst staining within the nuclei (see figure S1).…”
Section: T Cell Culture In Cell-free Supernatants From Mtbinfected Mamentioning
confidence: 99%